PENGARUH JOB STRESS DAN JOB INSECURITY TERHADAP TURNOVER INTENTION KARYAWAN RETAIL INDOMARET & ALFAMART SOLO RAYA - Silvia Novita Sari; Annastasya Aprilia; Aura Eri Ratna Mahesti; Dwi Ayu Ratnasih; Adelia Putri Istiqomah; Angely Cris Natalya (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of job stress and job insecurity on turnover intention among employees of Indomaret and Alfamart in the Solo Raya region. Utilizing a quantitative survey approach, data were collected from 384 respondents through a questionnaire employing a Likert scale as the measurement tool. Regression analysis results indicate that job stress significantly and positively affects turnover intention, with a regression coefficient of 0.492. Similarly, job insecurity also demonstrates a significant positive relationship, as reflected by a regression coefficient of 0.399. The R-squared value of 39.9% suggests that these two independent variables collectively explain variations in turnover intention, although external factors also play a role. These findings highlight that work-related stress and job insecurity are key determinants driving employees' desire to leave their organizations. Therefore, strategic efforts are required to manage the work environment effectively to mitigate the risk of turnover intention. This study offers significant practical implications for human resource management policy development, particularly in enhancing employee retention in the retail sector.